A comparative laboratory evaluation of the effectivity of 2% glutaraldehyde and 1 700 benzalkonium chloride in disinfecting used gloves among clinicians in the U.P. College of Dentistry - Mojica, Rosa Lynn S.; So, Elsie Y.
The purpose of this study is to compare the effectivity of 2% Glutaraldehyde and Benzalkonium Chrloride is disinfecting used gloves. This study also determined, by means of a biochemical test, whether the microorganisms obtained are pathogenic or non-pathogenic. Twenty senior clinicians from the U.P. College of Dentistry comprised the sample. The subjects used sterile gloves and performed scaling procedures on patients with chronic moderate gingivitis. An imprint of the right thumb was made on a agar plate prior to immediately after, and after washing with soap and water, the scaling procedure. The used gloves were immersed in solutions of 2% Glutaraldehyde and Benzalkonium Chrloride, then another imprint was made. Gloves which were immersed in 2% Glutaraldehyde show greater reduction in the number of colony forming units (CFU).
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Occupational health; Infection control, Dental; Antibacterial agent